2019
DOI: 10.1017/ice.2019.293
|View full text |Cite
|
Sign up to set email alerts
|

Nudging In MicroBiology Laboratory Evaluation (NIMBLE): A scoping review

Abstract: Background:Nudging in microbiology is an antimicrobial stewardship strategy to influence decision making through the strategic reporting of microbiology results while preserving prescriber autonomy. The purpose of this scoping review was to identify the evidence that demonstrates the effectiveness of nudging strategies in susceptibility result reporting to improve antimicrobial use.Methods:A search for studies in Ovid MEDLINE, Embase, PsycINFO, and All EBM Reviews was conducted. All simulated and vignette stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 27 publications
1
46
0
Order By: Relevance
“…These findings build on previous single-centre studies showing that suppressing specific urine culture and susceptibility results in hospitalized patients is associated with reduced antibiotic prescribing for asymptomatic bacteriuria [3,11] and reduced prescribing of targeted antibiotics such as fluoroquinolones [8]. Our study has confirmed this association between reporting and prescribing for both empirical and directed antibiotic prescribing, providing evidence to support selective reporting in a community setting.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These findings build on previous single-centre studies showing that suppressing specific urine culture and susceptibility results in hospitalized patients is associated with reduced antibiotic prescribing for asymptomatic bacteriuria [3,11] and reduced prescribing of targeted antibiotics such as fluoroquinolones [8]. Our study has confirmed this association between reporting and prescribing for both empirical and directed antibiotic prescribing, providing evidence to support selective reporting in a community setting.…”
Section: Discussionsupporting
confidence: 87%
“…Nudging is a term used to describe the concept of modifying choice architecture to augment decision-making without introducing incentives or inhibiting the autonomy of the decision maker [14]. Mounting evidence indicates that nudging is a promising intervention in the microbiology laboratory [8,15], but the lack of large-scale trials and specific guidance as well as insufficient resources have hindered its widespread implementation [7]. Future prospective trials and efforts to standardize selective reporting procedures may help to alleviate such challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, leveraging microbiology reporting to improve anti-infective utilization has been well described. Antimicrobial nudging interventions involve persuasive language or strategic cascading of susceptibility results in the microbiology reports to influence prescribing behavior without limiting provider autonomy (Langford et al, 2019). This, and the aforementioned studies using Vitek 2, explore how reporting lower MICs may affect prescribing practices resulting in the use of less expensive drugs without worsening patient outcomes, though secondary endpoints were not adequately powered in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The success of this intervention was further amplified using in-person and written education to ensure clinician adoption and understanding. Similar studies suggest that microbiology laboratory nudges and selective reporting effectively alter antimicrobial prescribing and optimize diagnostic test use [ 40 , 41 ]. Finally, for some diagnostics, evidence-based guidelines or protocols used at the point of care may help apply the microbiology results to clinical decision making and is therefore supported in the American Society for Clinical Pathology’s “Choosing Wisely” recommendations [ 42 ].…”
Section: Considerations For Post-analytic Diagnostic Stewardship Inte...mentioning
confidence: 95%